RESIDUAL PLATELET REACTIVITY TO ADP AND THE RISK OF BLEEDING IN STABLE CHD PATIENTS RECEIVING DOUBLE ANTIPLATELET THERAPY FOR ELECTIVE PERCUTANEOUS CORONARY INTERVENTION - E. V. Guskova; E. P. Panchenko; A. L. Komarov; A. B. Dobrovolsky; A. N. Samko (Российский кардиологический журнал)
Aim.  to study the significance of residual platelet reactivity (RPR) to adenosine diphosphate (ADP) and carriage of the gene cythochrome P450 CyP2C19 polymorphisms in relationship to the bleeding risk in stable CHD patients, undergoing planned PCI and receiving double antiplatelet therapy with aspirin and clopidogrel. Material  and  methods. In stable CHD patients after planned PCI we studied genotypes of polymorphic gene markers, related to clopidogrel metabolism (CyP2C19*1,*2,*3,*17) and studied RPR to ADP at clopidogrel treatment with Verifynow P2y12 analyzer (Accumetrics, США, San Diego, USA) at planned clinic visit in 5-12 months of treatment. Results. In CHD patients receiving double antiplatelet therapy for panned PCI during 12 months, minor clinically non-significant bleedings (MCNS) were the most prevalent, 51,1% noted them during follow-up, and major bleedings (MB) occured in 3,2%, minor clinically significant (MCs) — 9%. MCNS are the reason for DAT interruption in 14-15% patients after planned PCI. the value of RPR to ADP less than 205 PRU in stale CHD with aspirin and clopidogrel after planned PCI 7,8 times increases the risk of MCNS bleedings. In stable CHD with DAT after planned PCI during 12 months there was no any relationship of thrombotic outcomes and revascularization with the value of RPR to AdP.  there was relationship noted between the value of RPR to ADP and carriage of slowly functioning alleles of clopidogrel metabolism. MCNS are not related to major bleedings and reflect effectiveness of antiplatelet therapy, that is confirmed also by significantly lower rate of recurrent revascularizations due to restenosis and absence of stent thrombosis in the group of MCNSB.